Standardization of seed testing protocols and TZ test in muskdana (Abelmoschus moschatus) - UDAYA BHASKAR K.; S.S. PARIHAR; M. DADLANI; SHIV K. YADAV (Seed Research, 2026)
Muskdana is cultivated mainly for the aromatic oil extracted from seeds that emits an aroma resembling natural musk. The present study conducted on thirty samples of muskdana revealed that working sample size for physical purity and other crop seed determination was 40 g and 400 g, respectively. Seeds can be tested using rolled paper towel method at 25°C with first and final count (days) 6 and 12. Muskdana exhibited physical dormancy as considerable number of seeds did not imbibe water at the end of germination test and sulphuric acid treatment for 15 minutes was found to be an effective treatment in counteracting coat-imposed dormancy. Germination studies for three years revealed normal seedling percentage in muskdana varied from 11 to 64 in control and 17 to 86 in H₂SO₄ treatment for 15 minutes. Topographical tetrazolium chloride (TZ) test was also standardized for muskdana. Finally, seed standards were suggested based on our results of experimentation and perusal of standards in IMSCS (Indian Minimum Seed Certification Standards) of concerned family i.e.Malvaceae.